2018
DOI: 10.1007/s10753-018-0789-4
|View full text |Cite
|
Sign up to set email alerts
|

β4GalT1 Mediates PPARγ N-Glycosylation to Attenuate Microglia Inflammatory Activation

Abstract: The inflammatory activation of microglia has double-edged effects in central nervous system (CNS) diseases. The ligand-activated transcriptional factor peroxisome proliferator-activated receptor γ (PPARγ) inhibits the inflammatory response. β-1,4-Galactosyltransferase Ι (β1, 4GalT1) mediates N-glycosylation. In this study, the N-glycosylation of PPARγ, as well as two N-linked glycosylation sites in its DNA binding domain (DBD), was identified. Disruption of both sites by site-directed mutagenesis completely ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…11,16,17 Alterations of glycosylation of peroxisome proliferator-activated receptor c (PPARc) attenuate inflammatory activation of microglia. 18 Sialylation and fucosylation of N-linked and O-linked polysaccharides are altered in brain cancer, and these differences play critical roles in the progression of the cancer. 19 CSPGs are overexpressed in injured spinal cords and inhibit axonal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…11,16,17 Alterations of glycosylation of peroxisome proliferator-activated receptor c (PPARc) attenuate inflammatory activation of microglia. 18 Sialylation and fucosylation of N-linked and O-linked polysaccharides are altered in brain cancer, and these differences play critical roles in the progression of the cancer. 19 CSPGs are overexpressed in injured spinal cords and inhibit axonal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…One intriguing candidate protein is TNFR1, whereby α‐2,6 N ‐sialylation reportedly enhances pro‐inflammatory signaling on microglia [ 69 ]. Conversely, glycosylation of the microglia receptor CD200R is important for maintaining microglia in a homeostatic state upon interaction with neuronal CD200 [ 70 ] and N ‐glycosylation of peroxisome proliferator‐activated receptor γ suppresses microglia activation [ 71 ]. Several microglia‐associated N ‐glycoproteins are hyperglycosylated in AD, including Stabilin‐1, Intercellular Adhesion Molecule 1 (ICAM‐1), the NADPH oxidase (NOX2) component cytochrome b‐245, clusterin [ 20 ].Taken as a whole, our data supports an increase in N ‐sialylation may potentially modulate microglia functions within the plaque environment.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al showed that N-glycosylation of the peroxisome proliferator-activate receptor gamma (PPARγ) is crucial for the inflammatory activation of microglia [57]. Transfection of microglia with β-1,4-galactosyltransferase Ι (β4GalT1) attenuated the inflammatory activation of microglia through the N-glycosylation of PPARγ [57].…”
Section: Models Of Neuroinflammationmentioning
confidence: 99%
“…Liu et al showed that N-glycosylation of the peroxisome proliferator-activate receptor gamma (PPARγ) is crucial for the inflammatory activation of microglia [57]. Transfection of microglia with β-1,4-galactosyltransferase Ι (β4GalT1) attenuated the inflammatory activation of microglia through the N-glycosylation of PPARγ [57]. By contrast, Wang et al reported that β-1,4galactosyltransferase 5 (β4GalT5) is involved in the release of IL-1β from microglia stimulated by LPS [58] in vitro and in vivo.…”
Section: Models Of Neuroinflammationmentioning
confidence: 99%